An investigation of the influence of patient‐related factors and comedications on lamotrigine clearance in patients with epilepsy. (July 2016) - Baldoni, André Oliveira; Freitas‐Lima, Priscila; de Santi Ferreira, Flávia Isaura; Martinez, Edson Zangiacomi; Queiroz, Regina Helena Costa; Sakamoto, Americo Ceiki; Alexandre, Veriano; Perucca, Emilio; Pereira, Leonardo Regis Leira
Summary: Lamotrigine (LTG) is one of the most widely used antiepileptic drugs. Confusion still exists in the literature as to the relative influence of age, body weight, and concomitant drug therapy on LTG pharmacokinetics. So, the objective of this study is to evaluate the influence of patient‐related factors and comedication on LTG apparent oral clearance (CL/F). A therapeutic drug‐monitoring database was used to identify steady‐state plasma LTG concentrations in 210 patients. LTG CL/F values were calculated for each patient according to the equation CL/F (L/h per kg) = LTG daily dose (mg/kg)/Css (steady state concentration) (mg/L) × 24 h. A linear‐regression model was used to assess the influence of gender, dose, age, and body weight in LTG CL/F. The influence of comedication on LTG CL/F was investigated by applying the Bonferroni post‐test. The lowest LTG CL/F was found in patients comedicated with valproate (VPA) (mean, 0.0183 L/h per kg), followed by patients receiving VPA + enzyme inducers (0.0271 L/h per kg), patients on LTG monotherapy (0.0298 L/h per kg) and patients comedicated with enzyme inducers (0.056 L/h per kg) LTG CL/F correlated significantly with LTG dose ( P  < 0.01), but showed no significant relationship with gender, weight, and age. LTG CL/F is influenced by the type of antiepileptic comedication. The correlation with dose may be a spurious finding related to the fact that physicians, in adjusting dosage according to clinical response, are more likely to use larger doses in patients with high clearance values.